Grid optimization and demand side mangement for electric vehicles penetration in remote area - Zhang, Yixiao (2023)
The distributed power system in remote and rural area is the main challenges of the future smart grid development. Compared with traditional gasoline pipelines and gas station construction for fossil fuel vehicles, the high demand of Electric Vehicles (EVs) will then consider breaking their products in the market of remote areas. While the EVs adoption is growing globally, remote areas present unique challenges such as limited charging infrastructure, long transmission distances, and varying energy demands under the EVs penetration. This paper firstly defines the typical Remote Areas where the grid density is low with poor cable properties, but the future power demand is growing fast. Besides, their distributed energy is abundant and can contribute to generating electricity for the EVs, including solar energy, wind energy or marine energy. Renewable energy can maximize the reduction of carbon footprint and consumption. Then the Trincomalee city is selected as the simulation object.